The Role of Renaissance History on the Development and Promotion of Culture - Jing, Yuhan (Transactions on Social Science, Education and Humanities Research, 2024)
This essay investigates the role of Renaissance history in developing and promoting culture, highlighting its profound influence from the 14th to 17th centuries. The topic is critical as it lays the foundation for modern Western culture by reviving classical knowledge and fostering humanist ideals. The research addresses the gap in understanding how these historical transformations continue to shape contemporary society. The central question investigates the effects of the Renaissance cultural practice on modern religious, artistic, and intellectual expression. Using historical analysis, the essay reveals the enduring legacy of the Renaissance in democratising knowledge, promoting individualism, and challenging religious orthodoxy. This study focuses on the profound impact of Renaissance history on the development and promotion of culture from the 14th to the 17th centuries, a period marked by significant cultural transformations and the revival of classical knowledge. The significance of this study lies in understanding how the Renaissance laid the foundations for modern Western culture by fostering humanist ideals, democratizing knowledge, and challenging religious orthodoxy. These findings reiterate the contribution of the Renaissance to cultural and intellectual paradigms, pressing its relevance to modern cultural and educational contexts.